Load-Frequency Control of Multiarea Electric Power Systems. Review and New Challenges - F. Barrero González; M.I. Milanés Montero; E. González Romera; C. Roncero Clemente; P. González Castrillo (Revista Iberoamericana de Automática e Informática Industrial RIAI)
With the advent of liberalization in the interconnected power system, the operation based on market mechanisms and the gradual incorporation of renewable energy, the generation, transmission and demand roles are changing, while the load-frequency control mechanisms remain in their original form. This makes predictable arising training, research, development and innovation needs to meet new challenges.